Pharmacophore screening, molecular docking, and MD simulations for identification of VEGFR-2 and c-Met potential dual inhibitors - Dong, Junmin; Hao, Xiaohua (Frontiers in Pharmacology, 2025)
IntroductionThe vascular endothelial growth factor receptor 2 (VEGFR-2) and the mesenchymal-epithelial transition factor (c-Met) are critical in the pathogenesis and progression of various cancers by synergistically contributing to angiogenesis and tumor progression. The development of dual-target inhibitors for VEGFR-2 and c-Met holds promise for more effective cancer therapies that could overcome tumor cell resistance, a limitation often observed with inhibitors targeting a single receptor.MethodsIn this study, a computational virtual screening approach involving drug likeness evaluation, pharmacophore modeling and molecular docking was employed to identify VEGFR-2/c-Met dual-target inhibitors from ChemDiv database. Subsequent molecular dynamics (MD) simulations and MM/PBSA calculations were conducted to assess the stability of the protein-ligand interactions.ResultsFrom the virtual screening process, 18 hit compounds were identified to exhibit potential inhibitory activity against VEGFR-2 and c-Met. Among them, compound17924 and compound4312 possessed the best inhibitory potential according to our screening criteria.DiscussionThe analysis of the MD simulation results indicated that compound17924 and compound4312 showed superior binding free energies to both VEGFR-2 and c-Met when compared to the positive ligands. These findings suggested that both compounds were promising candidates for further drug development and could potentially serve as improved alternatives of cancer therapeutics.